Aspek Hukum Tanggung Jawab Pihak Perantara Kepada Konsumen dalam E-Commerce - Stella, Stella; Ginting, Budiman; O.K. Saidin; T.K.D. Azwar (Talenta Publisher, Universitas Sumatera Utara, 2022)
The activities of citizens and governments are increasingly through electronic system around the worlds. Improvement of information technology through electronic commerce has been implemented in Indonesia. Internet users in Indonesia in 2022 have reached around 210 million people who are related to the using of e-commerce. However, intermediaries as business actors still have weaknesses in conveying uncertain marketing information to their consumers. The research method used the prescriptive normative. The data analyzed the presumed liability of intermediaries to consumers in marketing information through e-commerce. This study explains the existence of e-commerce intermediaries who provide prices higher than the market price, the existence of e-commerce intermediaries who do not send the right goods that to be chosen by consumers, and e-commerce intermediaries aren’t provided clear confirmation to the seller for payments made by consumer. Legal liability is the main obligation of e-commerce intermediary, so it showed the development of technology and communication for the community. The presumed liability of the intermediary e-commerce in the application media to consumers, increasingly requires the validity of electronic contracts as transactions in e-commerce are carried out properly and legally communication continues to run smoothly to the seller so that the delivery of goods also has no errors from the seller to the consumer. The application of the concept of presumed liability that occur from application media or electronic systems is increasingly needed in Indonesia. Indonesia can also produce technology and communication developments, that enhanced the development of the national economy in society.